Internal energies and specific heats of condensed neon and argon system - Asger, Mohammed; Usmani, Q.N. (Elsevier, 1999)
We report results from molecular dynamic computations for internal energy and specific heat of condensed neon and argon systems in the temperature range 9-85 K modeled by Lennard Jones and Aziz potentials. Our motivation lies in the availability of direct experimental measurements of kinetic energies of these systems by deep inelastic neutron scattering experiments at various densities. The measured kinetic energies, specific heats and other thermodynamic quantities are calculated using Wigner Kirkwood expansion with terms of the O(Latin small letter h with stroke)6) in the expansion. We take advantage in using more realistic Aziz potential in our calculation. Neon results are in agreement with experiments at 18 K and above. Results are consistent with path integral Monte Carlo calculations over the entire temperature range considered and slightly higher than the effective potential Monte Carlo results. The kinetic energy results of solid argon are also consistent with self-consistent average phonon model calculations. The results are in quantitative agreement with experiment. © 1999 Elsevier Science B.V. All rights reserved.